Motivation and job satisfaction of human resources within an organization - Isac, Nicoleta; Badshah, Mian Waqar; Isac, Nıcoleta (University of Pitesti, 2016)
The purpose of this paper is of highlighting the link between motivation and job satisfaction. The research was started from a number of assumptions to show that the individual's expectations are related to motivation, while real rewards obtained by acts carried out are related to satisfaction. To achieve this goal was achieved an investigation on 68 employees using questionnaire method. The empirical basis of this paper is the interpretation’ results of all answers, obtained from the applied within the company questionnaire.
Keywords: Human Resources; Motivation; Job satisfaction